2022
DOI: 10.3126/ohjn.v2i1.47450
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression among College Students in Kathmandu, Nepal

Abstract: Introduction: Anxiety and depression are among the most common mental health problems, and they are highly comorbid with each other. Many college students experience several mental health issues because of academic pressure, family expectations, difficult environment, and controlling people. Hence, the objective of the current study was to investigate the prevalence of anxiety and depression in college students of Kathmandu, Nepal, as very limited studies have been conducted in this area. Methods: This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…According to a cross-sectional study conducted in Pakistan, mild, moderate, and severe anxiety symptoms were reported by 27.6%, 13.6%, and 6.5% of the students, respectively. 11 Study done in college of Kathmandu where the prevalence of anxiety in college students was 53.97% among that 28.57% student had mild anxiety, 18.85% had moderate anxiety, and 6.55% had severe anxiety 12 which is similar to our context.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to a cross-sectional study conducted in Pakistan, mild, moderate, and severe anxiety symptoms were reported by 27.6%, 13.6%, and 6.5% of the students, respectively. 11 Study done in college of Kathmandu where the prevalence of anxiety in college students was 53.97% among that 28.57% student had mild anxiety, 18.85% had moderate anxiety, and 6.55% had severe anxiety 12 which is similar to our context.…”
Section: Discussionsupporting
confidence: 82%
“…In our survey, 53.6% of male students reported having anxiousness which reflects opposite to the study done in Pakistan, females were more than male twice the rate 40% and 20%, 11 study in Kathmandu showed that female (62.03%) had higher prevalence of anxiety than male student (49.21%). 12 Our results suggest the prevalence of anxiety is higher in male students than female.…”
Section: Discussionmentioning
confidence: 60%
“…3 In a study done in Nepal among the students aged 15-21 years, more than 50% had varying severity of anxiety symptoms and about 40% had symptoms of depression. 4 Another study showed that about 50% of the medical students have some form of mental health problems. 5 As per mental health screening questionnaire, 64.7% (90/139) and 7.2% (10/139) participants reported somewhat difficulty and very much or extreme difficulty.…”
Section: Introductionmentioning
confidence: 99%